ANALISA FAKTOR PENYEBAB KERUSAKAN JALAN (STUDI KASUS RUAS JALAN W.J. LALAMENTIK DAN RUAS JALAN GOR FLOBAMORA) - Udiana, I Made; Saudale, Andre R.; Pah, Jusuf J. S. (Jurnal Teknik Sipil, 2014)
The roads is the most important land transportation in running all the economic activities with the other social activities, in case of road damages may gummed up the works of economic activities with the others social activity also may cause the road accident for the other road users. This research was aimed to find out the types of damage, the causal factor and the solution to prevent the road corruptness in W. J. Lalamentik street and in GOR Flobamora street. The kind of method used was field research by make use primary data of the road damage survey result in W. J. Lalamentik street dan GOR Flobamora street. The result survey of road damage in W. J. Lalamentik street dan the road in GOR Flobamora street were longitudinal cracks, transverse cracks, alligator cracks, edge cracking, meandering cracks, block cracks, corrugation, bleeding, delamination, potholes, patching. Generally causal factors of road damage are the increasing of traffic load volume, unwell drainage, unwell materials construction, climate ustable land condition, very thin ossification layer planning, the processing work that inappropriate with the specification. Based on the analysis result on the road damage happened in the field then the reparation action can be done with the per segment reparation action.